2020
DOI: 10.1038/s41598-020-57673-9
|View full text |Cite
|
Sign up to set email alerts
|

CR6-interacting factor 1 deficiency reduces endothelial nitric oxide synthase activity by inhibiting biosynthesis of tetrahydrobiopterin

Abstract: Downregulation of CR6 interacting factor 1 (CRIF1) has been reported to induce mitochondrial dysfunction, resulting in reduced activity of endothelial nitric oxide synthase (eNOS) and NO production in endothelial cells. Tetrahydrobiopterin (BH4) is an important cofactor in regulating the balance between NO (eNOS coupling) and superoxide production (eNOS uncoupling). However, whether the decreased eNOS and NO production in CRIF1-deficient cells is associated with relative BH4 deficiencyinduced eNOS uncoupling r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Aabed et al., (2019) in a study on the protective effects of BP on propionic acid (PPA)‐induced neuro‐inflammation in a rodent model of autism showed that BP can decrease systemic IL‐6, IFN‐γ and IL‐1α alongside increase IL‐10 and TNF‐α levels thereby suppressing the inflammatory pathways mediated by cytokines leading to proliferation and activation of immune cells from BM haematopoietic progenitor (HP) cells which ameliorating the neurotoxic effects of PPA. In an in vitro study of LPS‐Induced RAW 264.7 cells, Lee et al., (2020) showed that BP, in addition to its high antioxidant properties and reduced NO content, iNOS and cyclooxygenase‐2 (COX‐2), reduced IL‐1b, IL‐6 and TNF‐α levels as inflammatory mediators in macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aabed et al., (2019) in a study on the protective effects of BP on propionic acid (PPA)‐induced neuro‐inflammation in a rodent model of autism showed that BP can decrease systemic IL‐6, IFN‐γ and IL‐1α alongside increase IL‐10 and TNF‐α levels thereby suppressing the inflammatory pathways mediated by cytokines leading to proliferation and activation of immune cells from BM haematopoietic progenitor (HP) cells which ameliorating the neurotoxic effects of PPA. In an in vitro study of LPS‐Induced RAW 264.7 cells, Lee et al., (2020) showed that BP, in addition to its high antioxidant properties and reduced NO content, iNOS and cyclooxygenase‐2 (COX‐2), reduced IL‐1b, IL‐6 and TNF‐α levels as inflammatory mediators in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Colorimetric assay Abcam (Abcam Cat No: ab211083; Abcam, Cambridge, MA, USA) kits was used for measuring the serum nitric oxide synthases (NOS) activity according to the manufacturer's recommendations by using an ELISA Reader (Statfax 100, USA) at 540 nm and reported as U/ml of serum (Lee et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…After they were subjected to vortexing and sonication, the homogenized samples were centrifuged at 12,000× g for 15 min and the supernatant was harvested. Immunoblots were performed using 20 µg samples as described previously [ 15 ]. After electrophoresis and transferring to nitrocellulose membranes, blots were blocked using 5% skim milk over 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, CRIF1 is a potential target for mitochondrial dysfunction. CRIF1 deficiency impairs mitochondrial oxidative phosphorylation and reduces nitric oxide production while inhibiting tetrahydrobiopterin (BH4) biosynthesis enzymes such as guanosine triphosphate cyclohydrolase I, 6-pyruvoyltetrahydropterin synthase, sepiapterin reductase, and DHFR, leading to endothelial dysfunction [ 15 ]. DHFR regenerates BH4 from dihydrobiopterin and is an essential folate cycle enzyme required for homocysteine metabolism [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…BH4 treatment significantly increased myocardial BH4 and myocardial BH4/BH2 ratio BH4 is an important cofactor of NOS and is necessary for NO production. Insufficient BH4 leads to the decoupling of eNOS [16], generating a large amount of reactive oxygen species, which cause oxidative stress in the corresponding organs or tissues and promote heart failure. Therefore, we used high performance liquid chromatography to detect the concentration of BH4 in each group.…”
Section: Bh4 and Nebivolol Can Synergistically Improve Diastolic Dysfmentioning
confidence: 99%